Substantively smart cities: Participation, fundamental rights and temporality - Philipp Hacker; Jürgen Neyer (Internet Policy Review, 2023)
Smart city applications are increasingly deployed in urban spaces around the world. We contend that they only merit the attribute 'smart' if they embody what we term 'substantial smartness'. To develop this concept, we draw on both political and legal theories to show that citizen participation and activation, as well as respect for human and fundamental rights, are two essential dimensions of substantial smartness. Both dimensions, however, need to accommodate temporality, i.e., rapid changes in deployed technologies, their purposes and citizens' use of public infrastructure. By highlighting three examples and discussing smart city challenges to the GDPR, non-discrimination law and the proposed EU AI Act, we demonstrate that politics needs the law - and vice versa - to unlock the potential of substantively smart cities.
Keywords: 300; Smart cities; Data protection; Non-discrimination; Participation; AI governance